Poverty eradication through the implementation of good governance among the state government agencies in Kelantan, Malaysia - Zabidi, Nadirah (2024)
Poverty eradication remains one of the greatest challenges encountered by every country in the world, and the inefficiencies within the administration activities hinder the effectiveness of institutions. Even so, manifesting good governance practices could enhance service delivery and strengthen the governance system’s quality. Nonetheless, the main problem is that the inefficiencies within agencies in managing poverty eradication strategies have led to ineffective governance practices in Kelantan. Based on the concept of good governance, this study aims to uncover the status of poverty eradication and good governance in Kelantan, including elements of poverty eradication, ways to maintain effectiveness and the reasons for federal government interference in the relationship between poverty eradication and good governance. This study is about integrating elements of poverty eradication with good governance to enhance the quality of administration affairs in Kelantan. The quality of services for poverty eradication strategies depends on the level of efficiency of governance practices in its administration affairs. This study adopted a quantitative research approach. In this study, a descriptive research design is used to describe the situation accurately and the significance of the variables. The survey research design is used as the main instrument for this study. The data in this study were collected using an online-based survey method and structured interview. The findings obtained from the structured interview will be only used to support the main findings from the questionnaire survey. The findings from the interview gave supplementary information about the poverty eradication strategies initiated by each of the state government agencies. The respondents of this study are the public officials who are working in the state government agencies in Kelantan, which are the Kelantan’s Department of Social Welfare (JKMNK), Kelantan State Economic Development Corporation (PKINK), Kelantan State Chief Minister Corporation (PMBK), Council of the Religion Islam and Malay Custom Kelantan (MAIK), Southern Kelantan Development Board (KESEDAR) and Kelantan’s Community Development Department (KEMAS). This study has constituted that good governance practices have been observed as ‘negligence’ in their capability and capacity to eradicate poverty in Kelantan. Nevertheless, the idea has far outpaced its capability to carry out administrative activities, and it is important to highlight that the elements of good governance were not truly felt in practice, which is supported in this study, where the elements of good governance are not well demonstrated in practice. Having good governance is not the absolute remedy for eradicating poverty, but poor governance will deter the whole process of poverty eradication. Henceforth, the notion of practising ‘partial good governance’ has originated from the study, which, through emphasising the needs of the people and minimalising the good governance practice based on the contextual realities, the optimum level of effectiveness shall be achieved and could enhance the poverty eradication strategy to move forward progressively in the future. For this reason, practising ‘partial good governance’ overcomes the inefficiencies of the state government agencies in managing poverty eradication strategy in Kelantan.